Glycated Hemoglobin is a Significant Predictor of Femoral, but Not of Carotid or Popliteal, Intima-Media Thickness in Adolescents with Type 1 Diabetes: A Case-Series Study. (31st March 2023) - Ho, Hung-Chi; Lo, Fu-Sung; Lee, Jen-Kuang; Tsai, Wen-Yu; Su, Ta-Chen
Abstract : In healthy adults, the association between the glycated hemoglobin A1c (HbA1c) level and intima-media thickness (IMT) is stronger in the femoral artery than that in the carotid artery. However, whether this differential strength of association also applies to adolescents with type 1 diabetes (T1D) is unknown. Therefore, this study aimed to examine whether IMT increases in extracarotid arteries (specifically in the lower extremities) prior to the carotid artery. In total, 286 adolescents with T1D (15.9 ± 4.9 years; 42.0% male participants) were enrolled, and the B-mode ultrasonographic measurement of IMT in the carotid, femoral, and popliteal arteries was performed. Cardiovascular risk factors, including blood pressure (BP), body mass index, lipid levels, and glycemic parameters, were evaluated. To evaluate the site-dependent relationship between IMT and cardiovascular risk factors, a linear mixed-effects model was developed with repeated IMT measurements at various arterial sites as fixed effects and participants as random effects. Glycemic parameters, lipids, uric acid, high-sensitivity C-reactive protein, and advanced glycation end-products were some cardiovascular risk factors that worsened with increasing HbA1c levels. Patients with a higher HbA1c level (>10% vs. ≤10%) had thicker IMT in the femoral artery but not in the carotid or popliteal arteries. Patients with poorer diabetic control exhibited significant changes in certain cardiovascular functions, including central systolic BP, left ventricular (LV) ejection time, LV dp/dt max, stroke volume, and brachial artery compliance. A standard mediation analysis revealed that none of the aforementioned cardiovascular functions mediated the relationship between higher HbA1c level and greater femoral IMT. In adolescents with T1D, cardiovascular risk factors deteriorate with worsening blood glucose control. In the early stages of T1D, femoral IMT may serve as a more sensitive surrogate marker for hyperglycemia-induced subclinical atherosclerosis, an effect that may not be mediated by alterations in cardiovascular functions.